Деякі аспекти концептуалізації феноменів успіху й невдачі американськими й українськими мовцями в когнітивно-психологічному контексті (на матеріалі даних психолінгвістичного експерименту) - Калініченко, Віра Ігорівна; Kalinichenko, V. I. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті на основі даних психолінгвістичного експерименту проаналізовано деякі когнітивно-психологічні особливості концептуалізації феноменів успіху й невдачі носіями американської та української мовної свідо¬мості в контексті проблем власне мотивації, мотивації досягнення, ціннісно-цільового блоку особистості, само¬ефективності, екстернальних та інтернальних чинників реалізації/нереалізації запланованого, емотивних реф¬лексій на успішний і невдалий результат активності суб’єкта. In this article some cognitive-psychological peculiarities of the success and failure abstract phenomena conceptualization by the bearers of the American and Ukrainian linguistic conscience are observed. The problem under consideration is investigated on the basis of current psychological studies on success and failure categories and by the data obtained from the psycho¬linguistic experiment with American and Ukrainian speakers involved. In the piece of research the author determines the interrelation between the conceptual success and failure phenomena and the motivational aspect of the individual activity, and also the problems of self-efficacy, aim-and-value cluster of the action agent, external and internal factors of achieving or not achieving something planned, emotive reactions of the bearer of success or failure category to a positive or negative result of his/her activity in the process of goal achievement.
The Certain Aspects of Success and Failure Phenomena Conceptualization by American and Ukrainian Speakers (by the Psycholinguistic Experiment Results)
Keywords: успіх; success; невдача; failure; локус контролю; locus of control